2017
DOI: 10.1017/s0958344017000040
|View full text |Cite
|
Sign up to set email alerts
|

Eyetracking methodology in SCMC: A tool for empowering learning and teaching

Abstract: Computer-assisted language learning, or CALL, is an interdisciplinary area of research, positioned in tension between science and social science, computing and education, linguistics and applied linguistics. This paper argues that by appropriating methods originating in some areas of CALL-related research, for example, HCI or psycho-linguistics, the agenda of 'attention-focus' research can be shifted from a cognitive perspective to a learner-centred approach, understanding online language learning and teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…These results are in line with observations of Stickler and Shi (2017) in their study on online communication through a conferencing platform. Their findings showed that learners of the Chinese language looked most (70%) at content areas of the screen in which language teaching content is presented, followed with 20% of fixations directed towards social areas of the screen featuring the presence of participants (Stickler & Shi, 2017, p. 169).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in line with observations of Stickler and Shi (2017) in their study on online communication through a conferencing platform. Their findings showed that learners of the Chinese language looked most (70%) at content areas of the screen in which language teaching content is presented, followed with 20% of fixations directed towards social areas of the screen featuring the presence of participants (Stickler & Shi, 2017, p. 169).…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies in Synchronous Computer-Mediated Communication (SCMC) have recognised the benefits of using eye-tracking technology to study online language learning behaviour, albeit in combination with qualitative methods and as part of Mixed Methods Research (MMR) designs (O'Rourke, 2012;Stickler & Shi, 2017;Stickler, Smith, & Shi, 2016). Such a combination of methods not only facilitates the triangulation of data sets; it also allows for studies to incorporate participants' own perspectives into the interpretation of the data.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, however, there are reasons which lead us to believe that David indeed recalled his original thoughts. First of all, we observed the gaze-overlaid video to be a strong stimulus to recall mental processes as pointed out by Stickler and Shi (2017). Second, David was not only strong in mathematics but also exceptionally good in communicating: The descriptions he gave in the SRI indicated clearly that he was able to recall the original situation easilyan impression which is further supported by David using predominantly present tense when describing his approaches to work on the MST.…”
Section: Stimulated Recall Interview Using Gaze-overlaid Videosupporting
confidence: 64%
“…(Lyle, 2003, p. 861) In this study, we explore the creative process by carrying out an SRI with David using the previously recorded gaze-overlaid video, which displays David's gestures, writing, drawing, and eye movements, as stimulus. As a special type of "regular" video, gaze-overlaid videos are used to aid reflection (Stickler & Shi, 2017). Since they add the visual focus on actually examined areas, gaze-overlaid videos provide a particularly strong stimulus.…”
Section: Stimulated Recall Interview Using Gaze-overlaid Videomentioning
confidence: 99%
See 1 more Smart Citation